Interior design illustrated - Ching, Francis D. K., 1943-; Binggeli, Corky (2018)
"This book introduces complex concepts of interior design -- from defining interior space, elements and vocabulary of interior design to explaining interior environmental systems -- through his inimitable approach using words and drawings"--
Includes bibliographical references and index.
Keywords: Interior architecture; Space (Architecture); Interior decoration -- History -- 21st century